A preliminary screening and characterization of suitable acids for sandstone matrix acidizing technique: a comprehensive review - Leong, V.; Ben Mahmud, Hisham (SpringerOpen, 2018)
Matrix acidizing is a broadly developed technique in sandstone stimulation to improve the permeability and porosity of a bottom-hole well. The most popular acid used is mud acid (HF–HCl). It is a mixture of hydrofluoric acid and hydrochloric acid. However, one of the conventional problems in sandstone acidizing is that mud acid faces significant issues at high temperature such as rapid rate of reaction, resulting in early acid consumption. This downside has given a negative impact to sandstone acidizing as it will result in not only permeability reduction, but can even extend to acid treatment failure. So, the aim of this study is to provide a preliminary screening and comparison of different acids based on the literature to optimize the acid selection, and targeting various temperatures of sandstone environment. This paper has comprehensively reviewed the experimental works using different acids to understand the chemical reactions and transport properties of acid in sandstone environment. The results obtained indicated that fluoroboric acid (HBF4) could be useful in enhancing the sandstone acidizing process, although more studies are still required to consolidate this conclusion. HBF4 is well known as a low damaging acid for sandstone acidizing due to its slow hydrolytic reaction to produce HF. This would allow deeper penetration of the acid into the sandstone formation at a slower rate, resulting in higher porosity and permeability enhancement. Nevertheless, little is known about the effective temperature working range for a successful treatment. Considering the pros and cons of different acids, particularly those which are associated with HF and HBF4, it is recommended to perform a comprehensive analysis to determine the optimum temperature range and effective working window for sandstone acidizing before treatment operation. Prior to sandstone acid stimulation, it is essential to predict the feasibility of acid selected by integrating the effects of temperature, acid concentration and injection rate. Therefore, this manuscript has thrown light into the research significance of further studies.